Introgression of transgenic events and accompanying sequences into Mexican maize varieties - Siller-García, Jessica Nallely; Cruz-González, Miguel Ángel; Castillo-Reyes, Francisco; Rodríguez-Herrera, Sergio Alfredo; Morlett-Chávez, Jesús Antonio; Aguilar, Cristóbal N.; Rodríguez-Herrera, Raúl (Ecosistemas y Recursos Agropecuarios, 2023)
Representative seed samples of 215 of maize varieties from four (Jalisco, Michoacán, Oaxaca and Puebla) Mexican States were collected. The total genotypes collected in each State were 53, 96, 46 and 20 samples, respectively. Each seed collection was geo-referenced, then seed was planted and leaf tissue was used for DNA isolation, after that a PCR analysis was performed to determine the presence or absence of eight accompanying sequences and nine transgenic events in the 215 maize genotypes. Results showed introgression of accompanying sequences and transgenic events (cry1Ab) into some maize varieties. The major proportion of cry1Ab residues was observed in maize samples from Puebla (70%) followed by that displayed in the Oaxaca samples (52%), while Jalisco samples showed 15 and 7.5% of the cry1Ab gene and ntpII accompanying sequence, respectively, and Michoacán samples exhibited 44 and 17.7% for cry1Ab gene and the accompanying sequence, respectively. These results supported for applicate corrective measures for to prevent the genetic contamination of Mexican maize varieties and to clean up out-of-type phenotypes that could be sources of contamination of transgenic genes within maize populations contaminated with transgenes.